End-stage kidney disease: a never healing wound leading to another never healing wound, renal cancer - Docs, Janos; Kovacs, Gyula; Peterfi, Lehel (Journal of nephrology, 2023)
Background: End-stage kidney disease and acquired cystic kidney disease are the final stages of chronic kidney disease, leading to loss of kidney function and frequent development of tumours. It has been suggested that an inflammatory microenvironment may be responsible for the progressive kidney remodelling and cancer development. Methods: Our aim was to analyse gene expression suggested to be involved in the remodelling of kidneys in end-stage kidney disease, and in the development of preneoplastic lesions and tumours. Immunohistochemistry was employed to assess the cellular localisation of different genes involved in these pathways on representative tissue sections. Results: Cellular (αSMA positive naïve activated fibroblasts, endothelial cells, macrophages) and non-cellular components (cytokines IL6, TGFβ, IL1β, CSF2, fibronectin, laminin, and matrix modifier proteases MMP9 and MMP12) of the inflammatory microenvironment were expressed in the kidneys of patients with end-stage kidney disease. IL6 and FN1 expressing naïve activated fibroblasts and recruited inflammatory cells were the most abundant cellular components of the inflammatory microenvironment. Conclusion: The progressive inflammatory and fibrotic processes in end-stage kidney disease have features recalling those of a never healing wound and may explain the frequent development of kidney cancer.
Veröffentlicht: 13. Juli 2023
Gesehen am 24.08.2023